ACase of Nimesulide toxicity in an Indian Child - G, Gupta; P, Tiwari; R, Ahlawat (Indian Journal of Pharmacy Practice)
A6-year old male child presented with fever for 4 days and he had received nimesulide (without prescription) for 4 days before coming to doctor. On examination, the patient was found to have jaundice and haematuria. The laboratory investigations indicated that the most probable cause for jaundice & haematuria was Nimesulide, since serological test were negative. This is the first case report from India of concomitant hepatic and renal toxicity in a child.